2019
DOI: 10.1021/acs.iecr.9b00661
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Synthesis of Poly(ethylene 2,5-Furandicarboxylate) from 2,5-Furandicarboxylic Acid: Steps toward Environmental and Food Safety Excellence in Packaging Applications

Abstract: Poly(ethylene 2,5-furandicarboxylate) (PEF) is considered today as a very promising biobased polymer for packaging applications. Most often, scientific literature describes synthetic procedures based on the transesterification of the dimethylester of the 2,5-furandicarboxylic acid, whereas this paper aims at studying the possibility of a practical and profitable synthetic route for PEF comprising a direct esterification stage of 2,5-furandicarboxylic acid. In that respect two catalysts, zinc acetate and alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 44 publications
3
59
0
Order By: Relevance
“…More and more PEF synthetic approaches are being studied and optimized, making use of different catalysts and reaction conditions, so that it can become more sustainable and less impactful in the environment (Carlos Morales-Huerta et al, 2016 ; Terzopoulou et al, 2017 ; Kasmi et al, 2018 ; Rosenboom et al, 2018 ; Banella et al, 2019 ; Chebbi et al, 2019 ; Maniar et al, 2019 ). In this vein different authors tested different catalysts in PEF synthesis, and in particular (Terzopoulou et al, 2017 ) tested the effects of different catalysts on PEF mechanical recyclability.…”
Section: Pef End-of-lifementioning
confidence: 99%
“…More and more PEF synthetic approaches are being studied and optimized, making use of different catalysts and reaction conditions, so that it can become more sustainable and less impactful in the environment (Carlos Morales-Huerta et al, 2016 ; Terzopoulou et al, 2017 ; Kasmi et al, 2018 ; Rosenboom et al, 2018 ; Banella et al, 2019 ; Chebbi et al, 2019 ; Maniar et al, 2019 ). In this vein different authors tested different catalysts in PEF synthesis, and in particular (Terzopoulou et al, 2017 ) tested the effects of different catalysts on PEF mechanical recyclability.…”
Section: Pef End-of-lifementioning
confidence: 99%
“…In this case, due to the chelating effect of nitrogen, the use of organometallic reagents leads to product mixtures (n-BuLi) 70 or to an inverse regioselectivity (EtMgBr) 71 terephthalate (PET). 72,73 Lignocellulose is converted into furfural on an industrial scale 74 and catalytic follow-up procedures have been reported to yield methyl furoate quantitatively. 75,76 Starting from methyl furan-2-carboxylate To demonstrate the scalability of our reaction, we repeated the synthesis of 4b on a gram-scale.…”
Section: Substrate Scope Of the Carboxylation Reactionmentioning
confidence: 99%
“…20,21 However, there is still great interest in replacing PET with PEF due to its superior barrier proprieties (e.g., towards O 2 and CO 2 ) and the importance of exploiting renewable feedstocks in place of petrochemically-derived precursors to help reduce CO 2 emissions. 22 Patel and co-workers have estimated that the greenhouse gas (GHG) emissions associated with PET production can be reduced by more than half by substituting terephthalic acid with FDCA. 23 This aspect, combined with the lower price of fructose compared to p-xylene, has the potential to deliver a process where both environmental impact and profitability are improved.…”
Section: Introductionmentioning
confidence: 99%